POLISH INSOLVENCY LAW TERMINOLOGY IN TRANSLATION INTO ENGLISH. A CASE STUDY OF THE TERM ZARZĄDCA - MATULEWSKA, Aleksandra (Comparative Legilinguistics, 2013)
The paper touches upon selected problems connected with translation of insolvency law terminology from Polish into English. The term zarządca has been used to illustrate its vertical and horizontal intertextuality in Polish and English language. The corpus composed of nortmative texts (Polish Act on Insolvency and Rehabilitation, British Insolvency Act, European Union Repulation on Insolvency Proceedings) and soft-law (INSOL guidelines, NATO regulations, etc.) has been compared to show how the context modifies the meaning of the term and requires applying different equivalents depending on the context acquired meaning. The author also presents dictionary equivalents which may be found in Polish-English legal dictionaries to illustrate the quandaries awaitingthe translator who is to render a translation of a text dealing with insolvency law.